Teaching Chinese Characters: The Challenges and Strategies of Addressing the Unique Aspects of Chinese Characters and Exploring Effective Pedagogical Approaches - Wang, Mingliang (International Journal of Sociologies and Anthropologies Science Reviews, 2025)
Background and Aim: Learning the Chinese language can be challenging but acquiring the characters is probably the most difficult. Teachers and students are likely to face various challenges in their journey to learn and master Chinese characters. This study examined the unique aspects of teaching Chinese characters and explored effective pedagogical approaches. The study also suggested specific pedagogical approaches that teachers can use in the classroom to make learning more effective. Materials and Methods: Data was collected using a systematic review of previous articles. A total of 80 articles were obtained from various databases, including ERIC, ResearchGate, ScienceDirect, EBSCO, and JSTOR. The articles were reduced to 23 based on the inclusion criteria that were used to remove duplicate articles, irrelevant topics, and dates falling outside the 10 years. The PRISMA model helped in evaluating and removing articles that did not meet the inclusion criteria. Results: Findings indicate that the main challenges involved in teaching Chinese characters include unique features of the characters taking longer to teach and master, tonal complexity, logographic language system, radical and phonetics complexity, difficulty in selecting pedagogical strategies, and student-related challenges. Conclusion: The pedagogical approaches that teachers can use in the classrooms include the phenomenographic approach, traditional approach, innovative approach, character-centered approach, and meaning-centered approach. The study suggests a combination of phenomenographic and innovative strategies as the most effective pedagogical approaches.